2022
DOI: 10.3390/info13100442
|View full text |Cite
|
Sign up to set email alerts
|

Secure Sensitive Data Sharing Using RSA and ElGamal Cryptographic Algorithms with Hash Functions

Abstract: With the explosion of connected devices linked to one another, the amount of transmitted data grows day by day, posing new problems in terms of information security, such as unauthorized access to users’ credentials and sensitive information. Therefore, this study employed RSA and ElGamal cryptographic algorithms with the application of SHA-256 for digital signature formulation to enhance security and validate the sharing of sensitive information. Security is increasingly becoming a complex task to achieve. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Comparing DL + CCE with other classifiers developed in comparable and contemporary works is provided as well (see Table 7) [59][60][61][62]. The confusion matrix serves as the primary source of most of the data mining parameters.…”
Section: Discussion Comparison and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing DL + CCE with other classifiers developed in comparable and contemporary works is provided as well (see Table 7) [59][60][61][62]. The confusion matrix serves as the primary source of most of the data mining parameters.…”
Section: Discussion Comparison and Resultsmentioning
confidence: 99%
“…Other chronic conditions, such as cancer, will be tested utilizing the context-aware framework that has been presented. According to [52][53][54][55][56][57], the suggested framework will be evaluated on a variety of quality of service (QoS), energy use [58][59][60][61], and social network service (SNS) in the cloud (Cloud) criteria.…”
Section: Future Research Results and Conclusionmentioning
confidence: 99%
“…Decryption, on the other hand, requires knowledge of the private key to recover the original message from the ciphertext [9]. Emmanuel A. Adeniyi et al [7] used RSA and ElGamal cryptographic methods, as well as SHA-256, to create digital signatures that improved security and validated the exchange of sensitive information. The study sought to authenticate shared data using SHA-256 and cryptographic techniques.…”
Section: El Gamalmentioning
confidence: 99%
“…The signature will be different for each file based on the file information, which guarantees that the electronic document is reliable, the signature was created by a known source, and the document has not been altered; selected verifiers only can recover and verify the file from the digital signature [28]. The digital signature can be done using one of the public key cryptosystems, RSA or ElGamal and many other systems [29,30]. Kritsanapong et al [31] showed that RSA is 100% accurate in both signing and checking procedures, and it completed these processes with a good performance rate.…”
Section: Rsa Algorithmsmentioning
confidence: 99%